PENGARUH CITRA PERUSAHAAN, KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMILIHAN PRODUK UNIT MIKRO MANDIRI TANGERANG CILEDUG 2 - Amarza, Rizqi Pratama (Universitas Mercu Buana, 2014)
Abstract. The objective of this research is to analyze the influence of corporateimage, service quality, and trust towards purchase decision of micro credit unit atMikro Mandiri Tangerang Ciledug 2. This research is a quantitative researchwhich both primary and secondary data were employed. Secondary data weretaken from journals and books. Primary data were gathered using questionairewhich were distributed to the target respondents using convenience samplingtechnique. From the sampling technique, a total of 100 respondents were gathered.The results of this research show that corporate image, service quality, and trusthave influences towards purchasing decisions of micro credit at Micro Credit UnitMandiri Tangerang Ciledug 2.Keywords: Corporate Image, Service Quality, Trust and Purchase Decision